Ocena wiedzy na temat opóźnionej bolesności mięśniowej w sporcie = Assessment of knowledge on delayed onset muscle soreness in sports - Kochański, Bartosz; Kałużny, Krystian; Kałużna, Anna; Hagner-Derengowska, Magdalena; Wołowiec, Łukasz; Zukow, Walery; Hagner, Wojciech (Journal of Education, Health and Sport, 2016)
Kochański Bartosz, Kałużny Krystian, Kałużna Anna, Hagner-Derengowska Magdalena, Wołowiec Łukasz, Zukow Walery, Hagner Wojciech. Ocena wiedzy na temat opóźnionej bolesności mięśniowej w sporcie = Assessment of knowledge on delayed onset muscle soreness in sports. Journal of Education, Health and Sport. 2016;6(1):241-250. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45351 http://ojs.ukw.edu.pl/index.php/johs/article/view/3345 https://pbn.nauka.gov.pl/works/710295 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 25.01.2016. Ocena wiedzy na temat opóźnionej bolesności mięśniowej w sporcie Assessment of knowledge on delayed onset muscle soreness in sports Bartosz Kochański1, Krystian Kałużny1, Anna Kałużna1, Magdalena Hagner‑Derengowska1,2, Łukasz Wołowiec3, Walery Zukow4, Wojciech Hagner1 1Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2Katedra Neuropsychologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 3II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 4Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Wstęp. Zjawisko bolesności mięśniowej jest poważnym problemem i wyzwaniem dla współczesnej medycyny sportowej. Wyróżnia się dwa typy bolesności mięśniowej: wczesną i opóźnioną. Bolesność mięśniowa wczesna występuje podczas wysiłku fizycznego i ustępuje po jego zakończeniu. Opóźniona bolesność mięśniowa (ang. DOMS – delayed onset muscle soreness) charakteryzuje się występowaniem szeregu dolegliwości ok. 24-48 godzin od wysiłku fizycznego utrzymujących się około 5-7 dni Cel pracy. Celem pracy jest ocena wiedzy na temat opóźnionej bolesności mięśniowej wśród osób uprawiających sport zawodowo oraz amatorsko. Materiał i metody. Badania przeprowadzono na grupie 50 sportowców (25 zawodowców i 25 amatorów) w wieku 27,38 (+- 7,53). Badania były przeprowadzone na osobach dorosłych posiadających pełną zdolność do czynności prawnych. Oceny wiedzy na temat opóźnionej bolesności mięśniowej w sporcie dokonano z wykorzystaniem autorskiej ankiety. Wyniki. 94% badanych doświadczyła opóźnionej bolesności mięśniowej i zna objawy związane z tym zjawiskiem. Większość badanych zna i stosuje formy redukcji i zapobiegania DOMS, jednak aż 74% wśród zawodowców oraz 90% wśród amatorów błędnie uważa kwas mlekowy za przyczynę powstawania opóźnionej bolesności mięśniowej. Nie wykazano korelacji pomiędzy poziomem wiedzy, a płcią, wiekiem oraz miejscem zamieszkania. Wiedza zawodowców na temat opóźnionej bolesności mięśniowej jest istotnie większa (p<0,05), niż wiedza amatorów. Wnioski. 1. Wiedza na temat opóźnionej bolesności mięśniowej wśród sportowców jest niedostateczna. 2. Większość sportowców nie ma wiedzy na temat mechanizmu powstawania opóźnionej bolesności mięśniowej, jednak zna i stosuje formy jej zapobiegania i redukcji. 3. Wiedza na temat opóźnionej bolesności mięśniowej jest istotnie większa u osób uprawiających sport zawodowo. Abstract Introduction. The phenomenon of muscle soreness is a serious problem and challenge for modern sports medicine. There are two types of muscle soreness: early and delayed. Early muscle soreness occurs during physical exertion and relieved after its completion. Delayed onset muscle soreness is characterized by the presence of a series of ailments approx. 24-48 hours of exercise sustained about 5-7 days. Aim of the study. The aim of the study is to evaluate knowledge on delayed onset muscle soreness in sports. Materials and methods. The study was conducted on a group of 50 athletes (25 professionals and 25 amateurs ) aged 27.38 (+ - 7.53). Studies have been conducted on adults with full legal capacity. Assessment of knowledge on delayed muscle soreness in sports has been using the author’s survey. Results. 94% of patients experienced delayed onset muscle soreness and they know the symptoms associated with this phenomenon. The majority of respondents know and apply the form of reducing and preventing DOMS, but 74% professionals and 90% amateurs incorrectly believe lactic acid as the cause of delayed onset muscle soreness. There was no correlation between the level of knowledge and gender, age and place of residence. Knowledge professionals on delayed muscle soreness is significantly higher (p <0.05) than knowledge amateurs. Conclusions. 1. Knowledge of delayed muscle soreness in athletes is insufficient. 2. Most of athletes do not have knowledge about the mechanism of delayed muscle soreness, but know and apply the forms of its prevention and reduction. 3. Knowledge of delayed muscle soreness is significantly higher in people practicing sport professionally. Słowa kluczowe: opóźniona bolesność mięśniowa, ocena wiedzy. Keywords: delayed muscle soreness, assessment of knowledge.